Python deep learning : exploring deep learning techniques and neural network architectures with PyTorch, Keras, and TensorFlow /: exploring deep learning techniques and neural network architectures with PyTorch, Keras, and TensorFlow. (2019) - Vasilev, Ivan; (Computer engineer), Slater, Daniel; Spacagna, Gianmario; Roelants, Peter; Zocca, Valentino
No abstract available